LENGTH-WEIGHT RELATIONSIDP OF A HILL-STREAM FISH, GL YPTOTHORAX TELCHITTA (HAM.) FROM SAPTAKOSHI RIVER OF NEPAL - GHOSH, TAPAN KUMAR; SUBBA, BHARAT RAJ (Journal of Indian Fisheries Association, 2015)
The length-weight relationship of a hill-stream fish, Glyptothorax telchittafrom Saptakoshi river of Nepal was analysed using the formula W=aLh. Theexponential values computed for total length and standard length in relationto body weight were 2.991 and 2.888 respectively.Key words; Hill-stream fish, Glyptothorax telchittaLength-weight relationshipÂ« Nepal.